The Effects of Economic Growth and Investment and Inflation on Unemployment and Poverty in Indonesia - Sumarlina Sumarlina; Michael Michael; Diana Lestari (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The purpose of this study was to analyze and determine the effect of economic growth and investment and inflation on exhaustion and poverty in Indonesia. In this research, the analysis tool used was path analysis assisted by the Amos Version 22 program application. This research is a quantitative study using secondary data obtained from the Indonesian Statistics Agency in the form of time series data (2013-2022). The results of the first structural analysis of economic growth show a negative and significant value for stimulation, while investment and inflation show a negative value for activation. The results of the analysis of the second structure of economic growth with stimulation show a significant negative and positive effect on poverty. Economic growth shows a significant negative effect on poverty. Investment shows a significant negative effect on poverty. Inflation shows a significant positive effect on poverty. While suction shows a positive significance to dirtiness. Economic growth shows a positive value for the futility of response. Investment shows a significant negative value to the futility of the response. Inflation shows a significant negative value on poverty through responses.